2011
DOI: 10.1007/bf03395757
|View full text |Cite
|
Sign up to set email alerts
|

Postreinforcement Pause Duration Varies Within a Session and With a Variable Response Requirement but Not as a Function of Prior Revolutions

Abstract: The current study examined the variables that influence postreinforcement pause (PRP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Third, our aerobic exercise treatment was limited to a total of 6 hours (3 light: 3 dark). Although rats are more active in the dark cycle, Belke 63 demonstrated that when rats were restricted in the amount of time they had access to a running wheel, the light:dark period had no effect on the amount of time spent exercising. Future studies are needed to explore the effects of longer running periods, alone and in combination with other behavioral treatments, to investigate its potential beneficial role in forelimb recovery after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our aerobic exercise treatment was limited to a total of 6 hours (3 light: 3 dark). Although rats are more active in the dark cycle, Belke 63 demonstrated that when rats were restricted in the amount of time they had access to a running wheel, the light:dark period had no effect on the amount of time spent exercising. Future studies are needed to explore the effects of longer running periods, alone and in combination with other behavioral treatments, to investigate its potential beneficial role in forelimb recovery after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions (Belke 2010(Belke , 2011Belke and Pierce 2009;Belke et al 2006;Collier and Hirsch 1971;Iversen 1993;Premack et al 1964), investigations of wheel running as a reinforcer have used interval and response-initiated interval schedules.…”
mentioning
confidence: 99%